Reciprocal Evolution of Opiate Science from Medical and Cultural Perspectives - Stefano, George B; Pilonis, Nastazja; Ptacek, Radek; Kream, Richard M (Medical science monitor, 2017)
Over the course of human history, it has been common to use plants for medicinal purposes, such as for providing relief from particular maladies and self-medication. Opium represents one longstanding remedy that has been used to address a range of medical conditions, alleviating discomfort often in ways that have proven pleasurable. Opium is a combination of compounds obtained from the mature fruit of opium poppy, papaver somniferum. Morphine and its biosynthetic precursors thebaine and codeine constitute the main bioactive opiate alkaloids contained in opium. Opium usage in ancient cultures is well documented, as is its major extract morphine. The presence of endogenous opiate alkaloids and opioid peptides in animals owe their discovery to their consistent actions at particular concentrations via stereo select receptors. In vitro expression of morphine within a microbiological industrial setting underscores the role it plays as a multi-purpose pharmacological agent, as well as reinforcing why it can also lead to long-term social dependence. Furthermore, it clearly establishes a reciprocal effect of human intelligence on modifying evolutionary processes in papaver somniferum and related plant species.
Keywords: kojenec; anestetika; Anesthetics; Infant; Administration, Oral; Analgesics; aplikace orální; kultura; Analgesics, Opioid; Culture; lidé; analgetika; Humans; opioidní analgetika